PENGARUH MOTIVASI KERJA JURU PUNGUT RETRIBUSI PARKIR TERHADAP KEPUASAN PENGGUNA JASA PADA UPT PERPARKIRAN DAN KETERMINALAN DINAS PERHUBUNGAN LOMBOK BARAT - Aryani, Menik (Universitas Pendidikan Mandalika, 2022)
Abstract: Parking retribution is one of the potentials that du manages to be a source of regional revenue originating from within its territory. It becomes a benchmark in assessing the level of regional original income obtained by the region.The purpose of this study is to determine the mechanism of supervision of parking retribution collection by the West Lombok. This research is quantitative research that leads to Parking retribution is one of the potentials managed to be a source of local revenue originating from within the region. parking levy is one of the potentials managed to be used as a source of regional revenue originating from within the region. The purpose of this research is to find out the mechanism of collecting mechanism of parking retribution collection by Transportation Agency of Medan City, to know the to know the supervision conducted by Transportation Agency toward the collection of parking retribution in Lombok City, to know the obstacles and efforts in the implementation of parking levy collection in lombok City, to know the obstacles and efforts in the implementation of parking levy implementation of parking retribution collection in Lombok City. This research is descriptive analysis which leads to juridical research. This research is descriptive analysis that leads to empirical juridical research. Source of data The sources of data in this research are primary data and secondary data. Primary data is data obtained directly from research in Medan City Transportation. Tool Data collection tools are library research and field research. Based on the result of the research, it is understood that the mechanism of collecting levy collection mechanism by the Medan City Transportation Agency through the Medan City Technical Implementation Unit (UPT) parking which cooperates or provides parking fees. Technical Implementation Unit (UPTD) of Medan City which cooperates or gives the parking levy to a third party in managing the parking lot through the parking system.to third parties in managing parking through auction system and appointment system parking Keywords: Motivation, Parking Attendant, Service User Satisfaction Abstrak: Retribusi parkir merupakan salah satu potensi yang di kelola dijadikan sumber penerimaan daerah yang berasal dari dalam wilayahnya, hal tersebut menjadi tolak ukur dalam menilai tingkat pendapatan asli daerah yang di peroleh wilayah tersebut. Tujuan penelitian ini adalah untuk mengetahui mekanisme pemungutan retribusi parkir oleh UPT Perparkiran dan keterminalan dinas perhubungan Lombok barat, untuk mengetahui pengawasan yang dilakukan dinas perhubungan terhadap pemungutan retribusi parkir setiap kecamatan Lombok Barat ,untuk mengetahui hambatan dan upaya dalam pelaksanaan pemungutan retribusi parkir, metode yang digunakan dalam penelitian ini adalah metode kuantitatif, dan sumber data dalam penelitian ini adalah data primer dan data skunder, data primer yaitu data yang diperoleh secara langsung dari penelitian di UPT Perparkiran dinas perhubungan Lombok Barat, alat pengumpulan data adalah penelitian lapangan.Berdasarkan hasil penelitian dipahami bahawa mekanisme pemungutan retribusi parkir oleh dinas perhubungan melalui unit pelaksana teknis dinas(UPTD) Lombok barat, yang melakukan kerjasama atau memberikan kepada pihak ketiga dalam mengelola parkir melalui system lelang dan system penunjukkan, pihak ketiga yang bekerjasama dengan pemerintah daerah setelah memenuhi persyaratan diberika izin dan hak sebagai pengelola parkir, kemudian dalam pengelolaan,pihak ketiga dengan pemerintah daerah setelah memenuhi persyaratan kerjasama diberi izin dan hak sebagai pengelola parkir, pihak ketiga memperkerjakan petugas parkir untuk memungut retribusi parkir, Keywords: Motivasi, Juru Pungut Parkir, Kepuasan Pengguna Jasa